2005
DOI: 10.1111/j.1442-2042.2005.01211.x
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of female acute urinary retention caused by an impacted pelvic mass

Abstract: We report two cases of acute urinary retention in women with an impacted pelvic mass. In both cases, all urinary symptoms resolved completely after the surgical removal of the mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
0
6
2
Order By: Relevance
“…Previous authors reported that urinary retention due to UL commonly occurs in early morning (early‐morning voiding difficulty or urinary retention) 7,14,15 . However, these findings were not obvious in our case.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Previous authors reported that urinary retention due to UL commonly occurs in early morning (early‐morning voiding difficulty or urinary retention) 7,14,15 . However, these findings were not obvious in our case.…”
Section: Discussioncontrasting
confidence: 70%
“…However, similar intermittent/transient worsening (retention) is observed during the day (in the morning, as mentioned above) and during a menstrual cycle (at the onset, in our case 1) in UL. These findings might well reflect the hormonal and circulatory/body‐position influences on the uterus 7,14,15 . As for storage‐phase symptom, we did not perform a bladder diary; therefore we could not reproduce the storage‐phase urodynamic findings of increased bladder sensation by a bladder diary in case 1.…”
Section: Discussionmentioning
confidence: 98%
“…Symptoms can consist of feelings of discomfort and pressure, but various lower urinary tract symptoms have also been reported. A number of case reports/series have documented the relationship between uterine fibroids and voiding dysfunction, including acute urinary retention [5][6][7]. An ultrasound study suggested that the presence of a posterior fibroid might displace the cervix anteriorly, causing compression of the bladder neck and resulting in bladder outlet obstruction and subsequent urinary retention [8].…”
Section: Introductionmentioning
confidence: 99%
“…A large fibroid may weigh down the uterus, causing acute retroversion and compression of the cervix against the proximal urethra. [5] This causes anterior deflection of the cervix and subsequent urethral compression. [6] As the fibroid enlarges, it may become incarcerated in the pelvis and may stretch urinary bladder affecting its function and contractility.…”
Section: Discussionmentioning
confidence: 99%